Hubungan Kecerdasan Spiritual dengan Stres Pasien TB Paru di Rumah Sakit Paru Jember - Yunita Eka Ratnasari; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Pustaka Kesehatan, 2021)
Tuberculosis is an infectious disease that attacks pulmonary parenchyma caused by Mycobacterium tuberculosis bacteria. Pulmonary Tuberculosis has physical, psychological, and social effects which result in the risk of stress. Tuberculosis patients need an ability to reduce the risk of stress with increasing spiritual intelligence. This research used an observational analytic design with cross-sectional and the sampling technique was consecutive sampling with 84 respondents. The data were taken by used the spiritual intelligence and DASS 42 questionnaire. The statistical test used was the Spearman test. The statistical test results obtained p-value <0,001 and strength (r=-0,806) which means a relationship between spiritual intelligence with stress. Based on the results, there is a relationship between spiritual intelligence with stress in Pulmonary Tuberculosis patients. Spiritual intelligence can activate emotional and intellectual intelligence. Emotional intelligence is the ability to control feelings and regulate mood to avoid stress. Intellectual intelligence is the ability to solve a problem so that spiritual intelligence can affect Pulmonary Tuberculosis patients’ emotions in reducing stress.